Desmoglein-4 deficiency exacerbates psoriasiform dermatitis in rats while psoriasis patients displayed a decreased gene expression of DSG4 - Moreno Sosa, María Tamara (2021)
Desmogleins are involved in cell adhesion conferring structural skin integrity. However, their role in inflammation has been barely studied, and whether desmoglein-4 modulates psoriasis lesions is completely unknown. In this study, we assessed the impact of desmoglein-4 deficiency on the severity of imiquimod (IMQ)-induced skin inflammation and psoriasiform lesions. To this end, desmoglein-4−/− Oncins France Colony A (OFA) with Sprague–Dawley (SD) genetic background were used. Additionally, human RNA-Seq datasets from psoriasis (PSO), atopic dermatitis (AD), and a healthy cohort were analyzed to obtain a desmosome gene expression overview. OFA rats displayed an intense skin inflammation while SD showed only mild inflammatory changes after IMQ treatment. We found that IMQ treatment increased CD3+ T cells in skin from both OFA and SD, being higher in desmoglein-4-deficient rats. In-depth transcriptomic analysis determined that PSO displayed twofold less DSG4 expression than healthy samples while both, PSO and AD showed more than three-fold change expression of DSG3 and DSC2 genes. Although underlying mechanisms are still unknown, these results suggest that the lack of desmoglein-4 may contribute to immune-mediated skin disease progression, promoting leukocyte recruitment to skin. Although further research is needed, targeting desmoglein-4 could have a potential impact on designing new biomarkers for skin diseases.